الاستثمار في الأسهم في الأسواق المالية بالمالديف : دراسة تقويمية في ضوء الفقه الإسلامي - عبد اللطيف، محمد عياض (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
Different types of financial institutions which are unknown to early Islamic scholars have appeared in contemporary economic system. The most important among them is Share market. It is a company in which a group of people unknown to each other take part in mega trading projects that are not possible without a big capital. There were people with small capital searching for a way to increase their capital and to expand their business. As the result, there were many financial institutions especially the share market which gives an opportunity to them to attain their goal through collective investment. The Maldivian society which is a hundred percent Muslim is suffering from lack of shariah-based system to control business and trading companies. As these companies operate on interest-based economy through establishing strong connection with conventional banks, the more pious people who are serious in practicing Islam were complaining and avoiding the share market totally. Islamic scholars have different opinions on this particular issue. Some of them, who made their decision from Maqasid perspective, allow participation in interest-based share market with certain rules and conditions. According to them, non-participation of pious people brings terrible consequence in the finance sector. The scholars who forbid the participation of Muslims in the existing system are concerned with its connection to conventional banking system. The question is whether they can be allowed to benefit from those who do not seriously practice Halal and Haram or let them take part in this system with the hope of increasing their numbers to get the majority. The majority has the power to change to Islamic system. This research aims to find the solutions to a number of issues raised by the Maldivian people on financial institutions and its practices in the light of Shariah and Islamic law.